Lensless digital holographic microscopy as an efficient method to monitor enzymatic plastic degradation. (February 2021) - Schnitzler, Lena; Zarzycki, Jan; Gerhard, Marina; Konde, Srumika; Rexer, Karl-Heinz; Erb, Tobias J.; Maier, Uwe G.; Koch, Martin; Hofmann, Martin R.; Moog, Daniel
Abstract: A big challenge of the 21st century is to cope with the huge amounts of plastic waste on Earth. Especially the oceans are heavily polluted with plastics. To counteract this issue, biological (enzymatic) plastic decomposition is increasingly gaining attention. Recently it was shown that polyethylene terephthalate (PET) can be degraded in a saltwater-based environment using bacterial PETase produced by a marine diatom. At moderate temperatures, plastic biodegradation is slow and requires sensitive methods for detection, at least at initial stages. However, conventional methods for verifying the plastic degradation are either complex, expensive, time-consuming or they interfere with the degradation process. Here, we adapt lensless digital holographic microscopy (LDHM) as a new application for efficiently monitoring enzymatic degradation of a PET glycol copolymer (PETG). LDHM is a cost-effective, compact and sensitive optical method. We demonstrate enzymatic PETG degradation over a time course of 43 days employing numerical analysis of LDHM images. Highlights: Enzymatic degradation of plastic film was analyzed via digital holographic microscopy. Lensless microscopy is capable to monitor PET degradation. Non-destructive testing of biological plastic degradation is possible via this method. PET degradation by recombinant PETase was demonstrated over a time course of 43 days.